Rainbow Flags Over Margaret Court Arena: Commemoration vs. grassroots LGBTQ social activism at the Australian Open tennis championships. Issue 1 (1st July 2019) - Tredway, Kristi
At the 2012 Australian Open tennis tournament, fans created a social movement in response to Margaret Court's stance against marriage equality that she publicly stated in December 2011. 'Rainbow Flags Over Margaret Court Arena' was a loosely formed collective of people who used a Facebook page to organize. Court, now a fundamentalist minister with her own church, has, like so many fundamentalist Christians, likened homosexuality with sin. The actions of the 'Rainbow Flags Over Margaret Court Arena' group primarily involved being spectators at the Australian Open, in Margaret Court Arena, while waving or being adorned in rainbow flags. The enthusiasm and actions from this group compelled Laura Robson and Martina Navratilova to wear a rainbow headband and rainbow-adorned polo shirt, respectively, during their matches, and compelled Court and Navratilova to post full-page responses in the Melbourne newspaper. The friction between Court, Navratilova and Billie Jean King has its origins in the 1960s. The historical underpinnings of this social movement include the squabbles between Billie Jean King, and later Martina Navratilova, lesbian icons of women's tennis, and Margaret Court, a top player who was a contemporary of King.